Political Islam and human security - Mansouri, Fethi; Akbarzadeh, Shahram (Cambridge Scholars Press, 2006)
In the wake of the September 11 and subsequent terrorist attacks, the academic and media commentaries on Islam the religion and Islam the basis for political ideology haves received an unprecedented high level of exposure and attention.